Variabilidade espacial do tifton 85 em função dos atributos químicos e físicos do solo - Bier, Diogo Rafael (2013)
The aim of this study was to use Precision Farming tools to assess the spatial variability of production of green mass (MV), dry mass (MS) and accumulation of nitrogen (N), phosphorus (P) and potassium (K) of tifton 85 depending on the chemical and physical attributes of the soil in a small property. The study was conducted during the months of October to December 2012, in the municipality of Rio Grande do Sul-RS, Brazil View. The study was conducted in an area of 4.3 ha, divided into a grid of sampling 0.25 ha, resulting in 16 sampling points, where they performed two reviews for the determination of the spatial variability of the production of MV, MS and accumulation of NPK at tifton 85. For the presentation of this work the study was divided into two chapters, with the first, are presented the results of the survey of soil chemical attributes of layers: 0.00-0.10 0.10 0.20 m and 0.40 m 0.20-m, and its effect on the production of MV, MS and accumulation of NPK at tifton 85. In the second chapter studied the spatial variability of physical attributes of soil in layers of 0.00-0.35 m and its correlation with the production of MV and MS of tifton 85. The data obtained were submitted to descriptive statistics and correlation analysis by linear array of Pearson. From the results, it was concluded that the production of MV and MS and accumulation of NPK at tifton 85 feature a spatial variability considered of moderate to high. The base saturation was the only chemical soil attribute which showed correlation with the production of MS and MV of tifton 85. The values of N and P in tifton 85 MS, correlation with the chemical attributes of the soil base saturation, pH in water and H + Al. The physical attributes of the soil showed significant correlations with the production of MV and MS of tifton 85 were the ICPL, density and microporosity, being these more relevant as rainfall decreases.